Research of Interactive and Traditional Tasks Aimed at Studying Information Technologies among Students - Popkov S.I. (Психолого-педагогические исследования, 2021)
The results of a study conducted within the framework of an interactive approach to the task formation, which is an actual branch of computer methods in education, are presented. The author notes that the branch is currently not used for teaching information technologies practice in higher educational institutions due to the labor cost of forming, implementing and taking into account the impact of interactive tasks on the success of the educational process participants. The purpose of the study is to substantiate the introduction of relevant information technologies into the educational process, as well as approaches to the verification and formation of knowledge. It tested the main hypothesis: tasks aimed at interactive activity better help students in mastering the material, based on their own perception, than static tasks based on traditional approaches in the educational process with information technologies application. An intraindividual scheme of the experiment is used on the basis of traditional and interactive tasks, different types of tasks are presented to the same group of students. The sample for the participants of the experiment is recruited among the most capable students of the Information Technologies Faculty, bachelors, 2-4 year of experience according to the criterion of academic performance in the framework of specialized disciplines (28 people participated). The variables are empirically selected characteristics that reflect the useful qualities of the task in the context of the educational process. Methods of descriptive statistics are used to test hypotheses. It is noted that the results of the study make it possible to determine and formulate conditions that allow maximum use of the advantages of each of the studied types of tasks. The research confirms the demand for the development of teaching tools for students using interactive tasks, indicating the boundary conditions under which, according to the author, an interactive approach to the construction and implementation of tasks can demonstrate its effectiveness.